1995
DOI: 10.2337/diacare.18.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity, Fasting Plasma Insulin, and Blood Pressure in Japanese-Americans

Abstract: IAF correlated more strongly with blood pressure than BMI or skinfold thicknesses among older, second-generation Japanese-Americans and was positively correlated with blood pressure among Sansei independent of fasting insulin level. Fasting insulin was significantly correlated with blood pressure independent of visceral and overall adiposity among third-generation Japanese-Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 19 publications
3
71
0
1
Order By: Relevance
“…13,14,16,17 In 1995, it was reported in the Japanese Americans Community Diabetes Study that the effects of visceral adiposity on blood pressure were of statistical or borderline statistical significance in both second-and third-generation Japanese Americans, but after further adjustment for body mass index, these associations were diminished in the younger generation. 31 In 2003, it was reported in cross-sectional data from the same population that greater visceral adiposity was associated with a higher prevalence of hypertension independent of other measures of total or regional adiposity and fasting plasma insulin. 13 The reason for these different results was described to be partly because of the fact that in the earlier report, participants taking antihypertensive medication or having type 2 diabetes were not included, which by possibly truncating the upper range for blood pressure may have underestimated these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,16,17 In 1995, it was reported in the Japanese Americans Community Diabetes Study that the effects of visceral adiposity on blood pressure were of statistical or borderline statistical significance in both second-and third-generation Japanese Americans, but after further adjustment for body mass index, these associations were diminished in the younger generation. 31 In 2003, it was reported in cross-sectional data from the same population that greater visceral adiposity was associated with a higher prevalence of hypertension independent of other measures of total or regional adiposity and fasting plasma insulin. 13 The reason for these different results was described to be partly because of the fact that in the earlier report, participants taking antihypertensive medication or having type 2 diabetes were not included, which by possibly truncating the upper range for blood pressure may have underestimated these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have indicated a relationship between hypertension and visceral fat assessed by abdominal CT and WC, but US was not used in any of those studies (21)(22)(23)(24). Thus, in the present study, we assessed the usefulness of visceral fat assessment by US in outpatients.…”
Section: Introductionmentioning
confidence: 93%
“…This association is also clearly demonstrated in our Japanese-American cohorts from earlier studies. 44,45 It has been postulated that increased plasma FFA levels are associated with insulin resistance. 46,47 By releasing directly into the portal system a greater amount of FFA from enhanced triglyceride breakdown, as a result of greater catecholaminestimulated andaor reduced insulin-inhibited lipolysis, visceral fat may contribute more profoundly to the metabolic abnormalities seen with the insulin resistance syndrome.…”
Section: Discussionmentioning
confidence: 99%